Pelatihan Life Skill Tata Boga Kreasi Dan Estetika Dalam Plating Kuliner Khas Daerah Bagi Mahasiswa Program Studi Masyarakat Fakultas Keguruan Dan Ilmu Pendidikan Universitas Sriwijaya - Anisa Ramadona; Henny Helmi (JURNAL ILMIAH NUSANTARA, 2024)
This program aims to introduce Community Education Study Program students to life skills in the field of culinary arts, as well as develop their creative skills in creating regional culinary creations. This activity is expected to hone students' abilities in aesthetic aspects and culinary plating techniques. The form of activity carried out is training and mentoring in the field of culinary arts, involving lecturers and tutors who are experts in the culinary world. The main target of this activity is students of the Community Education Study Program, Faculty of Teacher Training and Education, Sriwijaya University. The activity was carried out in several stages, starting with the delivery of material about typical regional culinary plating, followed by the implementation of training which included discussion and direct practice. The implementation phase consists of an opening, presentation of material, joint culinary plating practice, as well as reflection and evaluation of the results of the training. There were 41 participants in the activity, and the results of this activity had a positive impact, namely increasing students' understanding of cooking and culinary plating, as well as developing skills. practical in this field. After this activity, it is hoped that students from the Community Education Study Program will be able to carve out a new dimension in the culinary world with aesthetic and independent plating skills.